Os fios da vida: Memórias e lutas de trabalhadores têxteis em Montes Claros/MG (1975-2008) - Leite, Valéria de Jesus (2010)
This study aimed to address issues relating to the experiences of textile workers in Montes Claros, MG. We have tried to expand our view of the working class, surpassing the relationship between the worker and the factory, to get to their way of life, examining in a closer way the social relationships that form between them and society, which led us to recognize the social diversity in a broader way. In this approach, what we did was try to get to know more about the worker s problems, not just their official organizations. Therefore, the emphasis was on how these workers live, what were their aspirations, values, how they dealt with problems related to housing, education, leisure and what meanings they gave to these achievements, how much importance they gave to religious questions and their involvement with problems from their neighborhood, how they socialized with each other at work and the importance it purchased in their lives and how their sociability spaces were formed. This way making it possible to address the movement of textile workers, their dreams, disappointments, it was essential for us to verify how they faced the day to day life issues in search for the establishment of territories of sociopolitical expression.